Evaluation of microcalcification contrast in clinical images for digital mammography and synthetic mammography. Issue 140 (July 2021) - Baldelli, P.; Cardarelli, P.; Flanagan, F.; Maguire, S.; Phelan, N.; Tomasi, S.; Taibi, A.
Highlights: Synthetic mammography is superior to digital mammography in microcalcs contrast. The contrast of microcalcs on synthetic images is on average 48 % higher. Contrast enhancement is achieved regardless the size and breast glandularity. Structure noise suppression increases microcalcs' contrast on synthetic images. A quantitative evaluation can better address the role of synthetic mammography. Abstract: Purpose: The aim of this work was to compare, in a clinical study, digital mammography and synthetic mammography imaging by evaluating the contrast in microcalcifications of different sizes. Methods: A retrospective review of microcalcifications from 46 patients was undertaken. A Hologic 3-Dimensions mammography system and a HD Combo protocol was used for simultaneous acquisition of the digital and synthetic images. Microcalcifications were classified in accordance with their size, and patient breast images were classified in accordance with their density as adipose, moderately dense and dense. The contrast of the microcalcifications was measured and the contrast ratio between synthetic and digital images was compared. An additional qualitative assessment of the images was presented to correlate the conspicuity of the microcalcifications with the suppression of the structure noise. Results: Microcalcifications in adipose background always exhibit a comparable or better contrast on synthetic images, regardless their size. For moderately dense background, synthetic images show a better contrast in 91.2 % of cases for small microcalcifications and in 90.9 % of cases for large microcalcifications. For a dense background, better contrast is seen in 89.5 % of cases for small microcalcifications, and in 85.7 % of cases for large microcalcifications. The contrast ratio increases with increasing breast glandularity. The suppression of structure noise also contributes to the enhancement of microcalcifications in the synthetic images. Conclusions: Synthetic mammography imaging is superior to digital mammography imaging in terms of microcalcification contrast, regardless their size and breast density.